Energy efficiency in cognitive cooperative amplify and forward networks. (December 2022) - Qin, Dong; Zhou, Tianqing
Abstract: The emphasis on improving energy efficiency has gradually replaced that on network throughput or data rate alone in the past, because the former not only concerns about network throughput or data rate, but also concentrate on energy consumption according to the goal of green and low carbon nowadays. In the context of increasingly clamoring environmental protection, this paper delivers the energy efficiency problem in amplify and forward cooperative relay networks, and then extends this problem to the cognitive radio scenarios. Traditional Dinkelbach parametrized method needs to transform the original problem into a series of nonlinear iterative problems. On the surface, this method simplifies the original energy efficiency optimization problem, but it often requires multiple iterations, and the number of iterations cannot be predicted in advance. In order to get rid of this dilemma, this paper directly starts with the partial derivative of the original problem, and obtains a closed-form solution of power distribution based on the Lambert function, instead of the water-filling form in traditional method. Then this Lambert result is extended to the cognitive radio cooperative relay system under the dual constraints of power budget and interference threshold. Finally, the performance of energy efficiency is confirmed by a large number of simulation experiments for distinct parameter settings.